2006
DOI: 10.1002/chem.200600248
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic States in Gas‐Phase Polypeptide Ions Revealed by 157‐nm Ultra‐Violet Photodissociation

Abstract: A new method of detecting the presence of deprotonation and determining its position in gas-phase polypeptide cations is described. The method involves 157-nm ultra-violet photodissociation (UVPD) and is based on monitoring the losses of CO2 (44 Da) from electronically excited deprotonated carboxylic groups relative to competing COOH losses (45 Da) from neutral carboxylic groups. Loss of CO2 is a strong indication of the presence of a zwitterionic [(+)...(-)...(+)] salt bridge in the gas-phase polypeptide cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 39 publications
7
60
0
Order By: Relevance
“…Trpcage was designed to fold quickly in water, yet previous work has shown that the 2+ charge state retains features consistent with the native fold in the gas phase [19,20]. However previous work also yielded conflicting results regarding the presence and location of salt bridges in the 2+ structure [38,39]. Our previous results for the 3+ charge state revealed significantly reduced EET relative to the 2+ charge state.…”
Section: C-trpcagementioning
confidence: 57%
“…Trpcage was designed to fold quickly in water, yet previous work has shown that the 2+ charge state retains features consistent with the native fold in the gas phase [19,20]. However previous work also yielded conflicting results regarding the presence and location of salt bridges in the 2+ structure [38,39]. Our previous results for the 3+ charge state revealed significantly reduced EET relative to the 2+ charge state.…”
Section: C-trpcagementioning
confidence: 57%
“…The 828 peak may have a small contribution from M-45 (loss of COOH from the precursor). Zubarev and coworkers have interpreted M-44 and M-45 fragments as indicative of whether the C-terminus is deprotonated by a zwitterionic structure [23]. While many of the same high-energy fragments are present when the peptide is dissociated with 157 nm light in the ion trap (Figure 4b), the x 9 and x 8 peaks are particularly dominant.…”
Section: Resultsmentioning
confidence: 99%
“…We suggested that the long observation timescale on this instrument makes additional fragments observable [20]. Zubarev and coworkers have also applied this technique to cleave disulfide bonds [21] and investigate peptide zwitterions in the gas-phase [22,23]. Morgan and Russell have compared 193 nm photodissociation in a tandem-TOF to their prior work using stepped reflectron voltages, and have studied some peptides with C-terminal arginine.…”
mentioning
confidence: 99%
“…The fit parameters in Table 4 indicate similar values for all species and charge states except the wild Trp-cage sequence for 1ϩ, suggesting that a salt bridge plays a role in only this species. These results are particularly interesting in light of ultraviolet photodissociation measurements [47] of Trp-cage in the 1ϩ charge state, which infer the presence of a salt bridge structure and MD calculations [48] on the 1ϩ state that characterize the Trp-cage structure with a salt bridge present.…”
Section: Trp-cage Proteinmentioning
confidence: 86%